The Combined Impact of Exhaled Nitric Oxide and Sputum Eosinophils Monitoring in Asthma Treatment: A Prospective Cohort Study - Malerba, Mario; Radaeli, Alessandro; Olivini, Alessia; Ragnoli, Beatrice; Ricciardolo, Fabio; Montuschi, Paolo (Current Pharmaceutical Design, 2015)
Background: Inhaled corticosteroids (ICS) treatment for asthma control is generally focused on lung function and symptoms, but inadequately correlated with airway inflammation. Objective: To compare asthma control in a group of patients whose treatment was based on fraction of exhaled nitric oxide (FENO) and sputum eosinophils (intervention group) with a group in whom treatment was based on clinical score (control group). Study design and primary outcome: Randomized parallel-group longitudinal 24-month study including 5 visits every 6 months. A combination of asthma exacerbation rate and symptom score at 24 months was the primary outcome. Participants: Fourteen patients with eosinophilic asthma per group were included. Results: In the intervention group, exacerbation rate/patient/year was reduced at 12 months (0.82) (-73%) and, to a greater extent at 24 months (0.5) (-84%) compared with baseline (3.21, p<0.01). In the control group, a significant reduction in exacerbation rate/patient/year was only observed between month 12 (3.0) and 24 (2.0, -33%, p<0.01). At 24 months, exacerbation rate was lower (-75%) in the intervention (0.5) than in the control group (2.0, p<0.05). Compared with baseline, mean symptom scores at 24 months were reduced in both groups (intervention group: -72%; control group: - 60%), but were lower in the intervention (8.1±1.0, p<0.05; -27%) than in the control group (11±2.6). ICS dose gradually increased in both groups throughout the study, with no between-group differences. Conclusion: Compared with conventional strategy, longitudinal monitoring of FENO and sputum eosinophils improves eosinophilic asthma control in terms of reduced symptoms and exacerbations without additional increase e in ICS treatment.
Keywords: asthma exacerbation rate